A fully quantum theory of high-gain free-electron laser. (13th September 2016) - Bonifacio, R.; Fares, H.
Abstract: The previous theory of high-gain free-electron laser (FEL) operating in the quantum regime is semiclassical because the electron dynamic is quantized but the radiation field is classically described. Here, we present for the first time a fully quantum-mechanical theory where also the field is quantized. We shall restrict to the FEL operation in the steady-state regime where the slippage length is much smaller than the bunch length. The results predicted by this theory are quite different from those of the semiclassical theory.